Association of the VEGF-1154G/A polymorphism with recurrent implantation failure in infertile Iranian women - Hamid Gourabi (Archives of Advances in Biosciences)
Introduction: Most IVF embryos fail to implant before clinical diagnosis. Successful implantation of an embryo relies on the endometrium forming a connection with the embryo, thereby enabling blood vessel formation and a suitable environment for the embryo to develop. Vascular Endothelial Growth Factor (VEGF) plays a vital role in angiogenesis. The role of VEGF polymorphisms, including VEGF1154 G/A (rs1570360), has been shown in recurrent implantation failure (RIF) in various ethnic groups. Materials and Methods: For this research, 148 healthy women with a previous successful pregnancy served as the control group, while the case group consisted of 75 women with Recurrent Implantation Failure (RIF) who had not achieved a pregnancy after transferring 10 embryos during three or more IVF cycles. Genomic DNA was extracted from peripheral blood cells. PCR was performed, and amplified DNA fragments were sequenced using the Sanger method. Results: After analyzing with SHEsis application, while the control group exhibited Hardy- Weinberg equilibrium (HWE), a deviation was observed in the case group. However, the chi- square test did not reveal a statistically significant difference between the groups. Conclusion: There was no significant association between this SNP and RIF in our case-control study. The presence of Hardy-Weinberg disequilibrium in the case group, despite the lack of significant difference from the control group, warrants further exploration of potential contributing factors and their implications for the study of this locus in relation to recurrent implantation failure.